2013
DOI: 10.36510/learnland.v7i1.630
|View full text |Cite
|
Sign up to set email alerts
|

Gay and Lesbian Families in the Early Childhood Classroom: Evaluation of an Online Professional Development Course

Abstract: Including families is an important theme in the early childhood classroom. Teachers, however, report feeling unprepared when a child’s family is composed of same-sex parents. Gay and lesbian families, in turn, feel invisible, silenced, and excluded. Overall, the topic is rarely covered in teacher education programs—in response, an online course on gay and lesbian families was developed. Teachers assessed the knowledge conveyed, comfort with the content, and helpfulness of the tools provided. The findings confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…The need for more training on LGBTQ issues has been a repetitive theme in the literature (Averett et al, 2017; Beren, 2013; Bower and Klecka, 2009). Training that is provided to the administrators at both levels; pre-service and in-service should be examined closely.…”
Section: Discussionmentioning
confidence: 99%
“…The need for more training on LGBTQ issues has been a repetitive theme in the literature (Averett et al, 2017; Beren, 2013; Bower and Klecka, 2009). Training that is provided to the administrators at both levels; pre-service and in-service should be examined closely.…”
Section: Discussionmentioning
confidence: 99%
“…Homoseksual berlaku di semua lapisan masyarakat di dunia dengan dianggarkan 21 peratus lelaki di dunia menjadi gay (Beren, 2013). Jabatan Kemajuan Islam Malaysia (JAKIM), melaporkan peningkatan gay hampir 100 peratus iaitu sebanyak 310,000 orang pada 2018 berbanding 173,000 orang pada 2017 (Berita Harian, 2018).…”
Section: Sorotan Literaturunclassified
“…Despite LGBTIQ parents’ accounts of insensitivity and stigma in ECEC settings (Cloughessy & Waniganayake, 2017; Cloughessy et al, 2017; Goldberg, 2014; Goldberg & Smith, 2014a), and EC educators’ self-reported need for training and resources on working with LGBTIQ-parented families (Beren, 2013; Church et al, 2018), limited research has focussed on the provision of pre- or in-service teacher training on meeting the needs of LGBTIQ-parented families (see, for example, Beren, 2013; Janmohamed, 2014; Riggs & Due, 2013). Somewhat counter-intuitively, it appears that even when EC educators hold positive attitudes towards LGBTIQ-parented families, they are less likely to act upon their stated attitudes (Hedge, Averett, White, & Deese, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reasons for the discrepancy between teacher attitudes, teacher practices, LGBTIQ-parented families’ perceived experience require further investigation, particularly in light of what appears to be a gap between what EC educators expect to learn from professional development and what LGBTIQ-parented families suggest EC educators in fact need to know. For example, EC educators have expressed resistance to adopting an explicit curriculum (Beren, 2013), yet LGBTIQ parents have recommended children’s picture books depicting LGBTIQ-parented families as an appropriate approach (Goldberg, 2014; Goldberg & Smith, 2014b). Similarly, challenging heteronormativity by adapting activities that have historically prioritised heterosexual family structures (such as Mother’s Day and Father’s Day) to include gender non-conforming families and thus promote a more inclusive parent community (Goldberg, 2014) appears to meet with resistance at times.…”
Section: Literature Reviewmentioning
confidence: 99%